Sustainable Property Management - Hopkins, Erin A. (Open textbook library., 2023)
Although “sustainability,” as used in the real estate context, is about preserving the environment, it is about more than that. In sustainable property management, sustainability encompasses three spheres—environmental, social, and economic. Sustainable property management is about reconciling these three spheres throughout the operations and maintenance phase of the building lifecycle in such a way that a balance is achieved between economic development and protection of environmental and social resources. This textbook explains how ecologically sustainable concepts may be implemented throughout the various property management operation functions while also considering the other spheres of sustainability. It also incorporates the theme of sustainable building practices as a human science as well as a building science by highlighting motivations and impacts to various stakeholders. The author draws on various industry examples to illustrate these concepts and provides many experiential activities for students to apply these concepts. Sustainable Property Management is intended for students majoring in property management and real estate at both the undergraduate and graduate levels. It can be incorporated into an existing property management operations course or used for a stand-alone course focused on sustainable property management. It is available online for free in multiple formats and also as an affordable print edition. Are you reviewing or adopting this book for a course? Please help us understand your use by completing this form https://bit.ly/interest_sustainable_property_management.